Durable remission of both multicentric Castleman's disease and Kaposi's sarcoma with valganciclovir, rituximab and liposomal doxorubicin in an HHV‐8‐positive, HIV‐negative patient. (28th October 2016) - Murphy, C.; Hawkes, E.; Chionh, F.; Chong, G.
Summary: What is known and objective: Human herpesvirus‐8 (HHV‐8)‐positive, HIV‐negative multicentric Castleman's disease is a rare lymphoproliferative disorder with no standardized treatment. Concurrent Kaposi's sarcoma, another HHV‐8‐related disease, is uncommon in HIV‐negative patients. The role of antiviral therapy and rituximab in HIV‐negative patients is not well established. Case description: We report a case of a 5‐year, durable remission of HHV‐8‐positive, HIV‐negative comorbid multicentric Castleman's disease and Kaposi's sarcoma treated with long‐term valganciclovir, following initial rituximab and liposomal doxorubicin. What is new and conclusion: Currently, there is no defined role for antiviral therapy in the treatment of HIV‐negative HHV‐8‐positive multicentric Castleman's disease and Kaposi's sarcoma. Ganciclovir followed by indefinite, continuous valganciclovir is thought to have contributed significantly to the durable response in this case. Abstract : HHV‐8 viral load correlates with disease activity for both Castleman's disease and Kaposi's sarcoma in a patient on long term valganciclovir.